Melanotic neuroectodermal tumor of infancy: Cytology and histopathology of a rare lesion at an uncommon site. Issue 2 (7th November 2016) - Batta, Nishant; Narang, Vikram; Kaur, Harpreet; Selhi, Pavneet Kaur; Sood, Neena
Abstract : Melanotic neuroectodermal tumour of infancy is a rare, pigmented neoplasm generally arising in infants during the first year of life. The cytological features are rarely described in the literature. This case due to its rarity and unusual site emphasising the cytopathological features and the necessity of histology for differentiating it from other round cell tumours has been presented. Diagn. Cytopathol. 2017;45:173–175. © 2016 Wiley Periodicals, Inc.